Pengaruh Pemberian Jus Buah Labu Kuning Cucurbita moschata (Duch.) Poir. Terhadap Tukak Lambung Tikus Putih Betina Yang Diinduksi Dengan Etanol Absolut - Suhatri Suhatri; Relly Sapta Rahmat Hura; Elisma Elisma (STIFARM Padang, 2011)
The effect of the pumkin juice Cucurbita moschata (Duch.) Poir. on the ulcer of white female rat induced by absolut ethanol was investigated using oral method. With The reseveral doses 0.4 ; 0.8 ; and 1.6 ml/200 g body weight doses. The result showed that the juice with 0,4, 0,8, and 1,6 ml/200 g body weight dose were able to cure the ulcer with curative ratio for each rasio dose are 22.22 %, 52.89 % and 71.04 %. It’s shows that higher dose give better result. The juice can also significantly decrease the gastric pH of rat induced by ethanol absolut to it’s normal value (P<0,05).